The State and the Grassroots Immigrant Transnational Organizations in Four Continents (Berghahn Books, 2015)
Whereas most of the literature on migration focuses on individuals and their families, this book studies the organizations created by immigrants to protect themselves in their receiving states. Comparing eighteen of these grassroots organizations formed across the world, from India to Colombia to Vietnam to the Congo, researchers from the United States, Belgium, France, the Netherlands, and Spain focus their studies on the internal structure and activities of these organizations as they relate to developmental initiatives. The book outlines the principal positions in the migration and development debate and discusses the concept of transnationalism as a means of resolving these controversies